‘Like an older family member’: Young Africans’ perceptions of Coca-Cola’s sugar-sweetened beverage brand in South Africa and Nigeria - Olutobi Akingbade (Consumer Behavior Review)
This paper, through an examination of the perceptions of a purposefully enlisted set of young Africans from Nigeria and South Africa, brings to the fore how Coca-Cola is embedded culturally and symbolically in the lives of these consumers, who liken the sugar-sweetened, multinational beverage to ‘an older family member’ and regard it as a ‘local’ drink and brand. The paper highlights how this has the propensity to enhance the enthusiastic and habitual consumption of Coca-Cola by these young Africans and their contemporaries with similar perceptions. Located within a qualitative research design, the study, amongst other reasons, was conducted against the backdrop of the surge in the consumption of sugar-sweetened beverages in Africa and other low- and middle-income countries and the increasing targeting of these regions by multinational food and beverage companies for their growth and profit, as consumers in the global north become more health aware.